2011
DOI: 10.1200/jco.2011.29.4_suppl.319
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemoradiation for resected gallbladder cancer.

Abstract: 319 Background: Gallbladder cancer (GBC) is the leading cause of cancer death in women in Chile. Even after curative surgery, prognosis is grim. To evaluate acute and late toxicity and efficacy in terms of overall survival of adjuvant chemoradiation (CR) after curative resection of GBC. Methods: We retrospectively analyzed the cohort of patients with curatively resected GBC diagnosed between January 1999 and April 2009, treated with adjuvant CR at the Instituto Nacional del Cáncer, Santiago de Chile. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…3 The second SR was composed of 10 PS with 816 patients; 4 and the third SR, analyzed 14 PS and 2405 patients. 15 The 24 observational studies consisted of 4 retrospective cohort studies, [16][17][18][19] with a total of 1772 patients; two PBCS (2867 patients), 20,21 and 18 retrospective PS (1130 patients). 2,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In all this represents a total of 55 studies and 9887 patients with GBC treated with curative surgical intent.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3 The second SR was composed of 10 PS with 816 patients; 4 and the third SR, analyzed 14 PS and 2405 patients. 15 The 24 observational studies consisted of 4 retrospective cohort studies, [16][17][18][19] with a total of 1772 patients; two PBCS (2867 patients), 20,21 and 18 retrospective PS (1130 patients). 2,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In all this represents a total of 55 studies and 9887 patients with GBC treated with curative surgical intent.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be specified that those who received adjuvant CT were younger, had less comorbidities and often presented positive lymph nodes, than those who received surgery alone. 16 In another retrospective cohort, it was also found that adjuvant treatments were effective, in terms of higher OS in subjects with positive lymph node disease (HR: 2.759 [1.14, 6.66]) 18 (type 4 treatment and prognosis 2b studies). Moreover, in a large series of retrospective patients with stage T2-3 N0-1 M0, treated with R0 surgery and adjuvant protocols of CT and CRT; it was observed that patients with T3 or positive lymph node disease, treated with adjuvant CT had a slight OS advantage (0.25 years more, p = 0.009), since OS curves converged at 5 years of follow-up.…”
Section: Effectiveness Of Adjuvant Treatments In Positive Lymph Node mentioning
confidence: 97%
See 3 more Smart Citations